The Influence of Mother’s Use of Technological Devices on Child’s Early Childhood Development in Bangladesh - Munira, Shirajoom; Nafisa, Sadia Afrin; Kibria, Gulam; Sutopa, Tasmia Sad (Dhaka University Journal of Science, 2025)
The study aims to explore the association between maternal ICT use and child development in Bangladesh along with examining other important factors influencing the outcome. Early childhood development (ECD) helps children to achieve their full potential providing strong foundations throughout the life. But, Bangladesh often faces challenges with ECD. On the other hand, the country has been progressively embracing ICT use due to rapid urbanization and drastic economic growth. However, the study includes 8726 recent births aged three to four years from Multiple Indicators Cluster Survey (MICS) 2019 data in Bangladesh considering ECD as a binary outcome variable and several background characteristics of respondents as predictors. 73.1% children are found developmentally on track. The main finding of the study is that the use of ICT by mothers keeps the ECD on track. From multivariate analysis, we found that children of mothers not using computer have 69.7% higher odds of delayed development than the children of mothers who used computer (p-value: 0.032). The children of mothers, who were not in touch with the internet experienced 49.9% higher odds of delayed development than the children of the ones who were in touch (p-value < 0.001). It is also noticed that the risk of delayed development is significantly 18.6% higher (p-value = 0.005) in the children, whose mothers did not own a mobile than the mothers who owned. Other factors like maternal education, media exposure, age and sex of child, division, child has something to play or read and ECD program attendance also influence the study outcomes. However, it is recommended, when preparing initiatives pertaining to children’s cognitive and physical development, the policymakers should take the study’s findings into consideration. These findings can also be utilized to achieve SDG target 4.2, which is to guarantee that all girls and boys have access to high-quality pre-primary education so that they are prepared for primary school by 2030. Dhaka Univ. J. Sci. 73(1): 1-11, 2025 (January)